Pendekatan Metaphorical Thinking Terhadap Kemampuan Pemahaman Konsep Matematika - Kristiawati, Kristiawati; Usman, Muhammad Rizal (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2024)
This study aimed to determine the effect of the application of the Metaphorical Thinking approach toward the ability to understand mathematical concepts of XI MA DDI Galesong Baru students in Makassar City. This type of research was a pre-experiment research. The population in this study amounted to 19 people. Then, the samples for this study were taken from all existing participants (saturated sampling), namely all students of class XI MA DDI Galesong Baru Makassar City, which were collected 19 people in the odd semester of the 2019/2020 school year. The data were collected by using tests and observation sheets of student activities. The analysis technique used was descriptive and inferential statistical analysis techniques. The results of descriptive statistical analysis showed that(1) the average pre-test ability of understanding mathematical concepts of students was 32.21 in the very low category,(2) the average post-test of students' understanding of mathematical concepts was 78.58 in the good category, (3) N-gain of 0.68 was in the medium category. Based on the results of the research above, it could be concluded that the application of the Metaphorical Thinking approach affected the ability of understanding the mathematical concepts of students of class XI MA DDI Galesong Baru, Makassar.